Perancangan UI/UX Aplikasi SISAKTI-NG Layanan Sistem Informasi Point SKP Universitas Udayana - Putra, Ananda; Santiyasa, I Wayan (Jurnal Nasional Teknologi Informasi dan Aplikasnya, 2023)
SISAKTI-NG is an information system for managing SKP ( Satuan Kredit Partisipasi ) at Udayana University. Currently, SISAKTI-NG is only available as a web-based application and does not have a mobile version. Based on a survey conducted among several Udayana University students, the author concluded that the website's interface of SISAKTI-NG is unattractive and dull. Therefore, the author is interested in designing the User Interface (UI) and User Experience (UX) for the SISAKTI-NG information system. Through this research, it is hoped that the SISAKTI-NG application can be improved in terms of its visual appearance to become more appealing and modern, meeting the needs and providing a comfortable user experience for Udayana University students. This research adopts prototyping and modeling methods. Based on the survey conducted, the calculation of the usability value of the UI/UX design of the SISAKTI-NG application which was tested using the SUS (System Usability Scale) method obtained an average SUS score of 77.25, NPS value with passive results, Acceptable, adjective value with results good, and the grade gets a B. This research has received positive reviews from SISAKTI-NG users when compared to the previous interface design.